Effectiveness and safety of nivolumab and ipilimumab in older adults with renal cell carcinoma: findings from a multicenter observational study in Poland - Drobniak, Artur; Stokłosa, Łukasz; Grela-Wojewoda, Aleksandra; Calik, Jacek; Versuti Viegas, Natalia; Dobrzańska, Jolanta; Roman, Agnieszka; Szwiec, Marek; Bidas, Anna; Tusień-Małecka, Daria; Gawlik-Urban, Angelika; Puskulluoglu, Mirosława; et al. (Frontiers in Oncology, 2025)
BackgroundNivolumab and ipilimumab (nivo+ipi) are recommended for treating metastatic clear cell renal cell carcinoma (mRCC), though their safety and efficacy in older adults remain uncertain. This study examines the outcomes of this regimen in Polish patients aged ≥65 years.MethodsIn this multicenter observational study, 138 patients with mRCC who received nivo+ipi between May 2022 and October 2024 were analyzed. Key outcomes included objective response rates (ORR), disease control rate (DCR), and progression-free survival (PFS) with comparisons between patients aged <65 and ≥65 years. Safety was assessed based on the incidence and severity of immune-related adverse events (irAEs). Survival outcomes were analyzed using Kaplan-Meier methods and Cox proportional hazards models, adjusting for potential confounders. A significance level of p < 0.05 was applied.ResultsAfter a median follow-up of 13 months, the median PFS for the entire cohort was 15.7 months (95% confidence interval [CI]: 10.2–20.8); in patients <65 years, it was 11.3 months, while in those ≥65 years, it was 23 months. Patients ≥65 years had a 40% lower risk of progression than younger patients (hazard ratio 0.6, 95% CI: 0.3–0.9, p=0.03). Patients aged ≥65 years exhibited a higher ORR (46.2% vs. 26%) and DCR (73.8% vs. 63%, p=0.02 for both). The overall incidence of irAEs was comparable between age groups; however, older patients experienced a higher frequency of very severe irAEs (1 vs. 6, p=0.06).ConclusionsThis study demonstrates that nivo+ipi are effective across age groups, with older patients achieving comparable or even superior outcomes with acceptable irAEs rates.